2012
DOI: 10.1051/0004-6361/201116752
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two tails and an off-centered envelope: diffuse light around the cD galaxy NGC 3311 in the Hydra I cluster

Abstract: Context. The formation of intracluster light and extended halos around brightest cluster galaxies is closely related to morphological transformation, tidal stripping, and the disruption of galaxies in clusters. Aims. Here we look for observational evidence to characterize these processes, by studying the morphology and kinematics of the diffuse light in the core of the Hydra I cluster. Methods. With V-band surface photometry, we derive the structural parameters (Sersic index n, effective radius R e , b/a, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
149
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(171 citation statements)
references
References 43 publications
22
149
0
Order By: Relevance
“…Observations show that the red GC populations have numberdensity profiles consistent with that of the stars in the parent galaxy, while the blue GCs are spatially more extended in the intracluster space and trace the metal-poor component of the halo (Forbes et al 2012;Pota et al 2013;Durrell et al 2014;Cantiello et al 2015;Hilker et al 2015). In the Hydra cluster, the location of blue GCs coincides with a group of dwarf galaxies under disruption, suggesting a young stellar halo that is still forming (Arnaboldi et al 2012;Hilker et al 2015). In this case, this interpretation is further supported by kinematic measurements.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Observations show that the red GC populations have numberdensity profiles consistent with that of the stars in the parent galaxy, while the blue GCs are spatially more extended in the intracluster space and trace the metal-poor component of the halo (Forbes et al 2012;Pota et al 2013;Durrell et al 2014;Cantiello et al 2015;Hilker et al 2015). In the Hydra cluster, the location of blue GCs coincides with a group of dwarf galaxies under disruption, suggesting a young stellar halo that is still forming (Arnaboldi et al 2012;Hilker et al 2015). In this case, this interpretation is further supported by kinematic measurements.…”
Section: Introductionsupporting
confidence: 52%
“…As pointed out in Section 1, several recent works have shown that the light profiles of BCGs are not uniquely and well fitted by a single Sérsic profile, where the intensity I R R n 1 ( ) µ , but in several cases a second component is needed to fit the outer stellar halo (Seigar et al 2007;Donzelli et al 2011;Arnaboldi et al 2012). For NGC1399, Schombert (1986) tried to fit the light profile with a single component using de Vaucouleur's law: the best fit matches very well only the inner and brighter regions of the galaxy for R 10 arcmin.…”
Section: Profile Fitting: the Exponential Halo Around Ngc1399mentioning
confidence: 99%
“…Luminosity-weighted stellar populations of the Hydra I cluster core: ages (left), metallicity (centre) and alpha-elements content (right). Upper and lower panels display contours for the V-band image and the offset envelope respectively, as in Arnaboldi et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Arnaboldi et al (2012) reported the existence of an faint surface brightness offset envelope. In part I of our work (see Hilker at al.…”
Section: Introductionmentioning
confidence: 99%
“…These events are possibly the mechanisms producing the diffuse halos around galaxies (Ibata et al 1994;Zibetti et al 2004;Arnaboldi et al 2012) or even the intragroup or cluster light (Mihos et al 2013;Zibetti et al 2005).…”
Section: Introductionmentioning
confidence: 99%